Water‐Induced Diamond Formation at Earth's Core‐Mantle Boundary. Issue 16 (18th August 2022) - Ko, Byeongkwan; Chariton, Stella; Prakapenka, Vitali; Chen, Bin; Garnero, Edward J.; Li, Mingming; Shim, Sang‐Heon
Abstract: The carbon and water cycles in the Earth's interior are linked to key planetary processes, such as mantle melting, degassing, chemical differentiation, and advection. However, the role of water in the carbon exchange between the mantle and core is not well known. Here, we show experimental results of a reaction between Fe3 C and H2 O at pressures and temperatures of the deep mantle and core‐mantle boundary (CMB). The reaction produces diamond, FeO, and FeHx, suggesting that water can liberate carbon from the core in the form of diamond ("core carbon extraction") while the core gains hydrogen, if subducted water reaches to the CMB. Therefore, Earth's deep water and carbon cycles can be linked. The extracted core carbon can explain a significant amount of the present‐day mantle carbon. Also, if diamond can be collected by mantle flow in the region, it can result in unusually high seismic‐velocity structures. Plain Language Summary: Carbon plays a vital role in geological processes occurring in the Earth's interior. While most carbon on Earth exists in its core, whether or not the core carbon can be added to the mantle is unclear due to the lack of knowledge of possible carbon transfer mechanism at the core‐mantle boundary (CMB). We conducted experiments by reproducing the extreme pressure and temperature conditions of the CMB. Our experiments show that water can react with the metallic iron core and liberate carbon as diamond, suggesting an important relationship between Earth's water and carbon cycles. In addition, our result predicts possible existence of diamond in some regions of the deepest mantle. Key Points: Water reacts with iron‐carbon alloy to form diamond at the P – T conditions expected for Earth's core‐mantle boundary Some of Earth's mantle carbon may come from the core through water‐induced reactions at the core‐mantle boundary Diamonds formed at the core‐mantle boundary may result in high seismic velocity structures in the region